Identification of Child and Youth Maltreatment at Emergency Departments - Salminen-Tuomaala, Mari; Tiainen, Juha; Paavilainen, Eija (European Journal of Applied Sciences, 2025)
The purpose of the study was to describe emergency department nursing staff’s ratings and experiences of identifying child and youth maltreatment. The study aimed at producing information that can be used in nursing to promote the detection of maltreated children and youth. The data was collected using a Webropol survey in autumn 2022 and spring 2023. The quantitative data was analysed using statistical methods and the qualitative data using inductive content analysis. The majority of the nursing staff at emergency departments rated their competencies in identifying physical child and youth maltreatment and neglect of care as rather good. In contrast, they did not assess their competencies in identifying psychological maltreatment as good. The emergency department staff were aware of factors associated with child and youth maltreatment, including parents’ lacking care skills, nutritional problems, signs of physical violence, neglect of a child’s medical care, and situations that threaten a child’s or youth’s mental and physical health.